2010
DOI: 10.1038/icb.2010.84
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 limits the expansion of immunoregulatory CD4CD8 T cells in autoimmune‐prone non‐obese diabetic mice

Abstract: Regulatory T cells appear to show great potential for use in cellular therapy. In particular, CD4 À CD8 À (double negative (DN)) T cells, which compose 1-3% of the total number of T lymphocytes, exhibit prominent antigen-specific immune tolerance properties and confer immune tolerance in models of allografts and xenografts. We have recently shown that autoimmunediabetes-prone mice carry fewer DN T cells and that this phenotype contributes to autoimmune-prone diabetes susceptibility, suggesting that increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 58 publications
(165 reference statements)
3
54
0
4
Order By: Relevance
“…Specifically, autoimmune-prone mice carry fewer DN T cells, and injection of DN T cells has been shown to be sufficient to reduce the incidence of autoimmune diabetes in two distinct TCR transgenic mouse models (21,22). Importantly, a low DN T cell proportion, rather than defects in DN T cell function, associates with diabetes susceptibility (22)(23)(24). Together, these observations suggest that variations in DN T cell proportion correlate with susceptibility to autoimmune diabetes.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Specifically, autoimmune-prone mice carry fewer DN T cells, and injection of DN T cells has been shown to be sufficient to reduce the incidence of autoimmune diabetes in two distinct TCR transgenic mouse models (21,22). Importantly, a low DN T cell proportion, rather than defects in DN T cell function, associates with diabetes susceptibility (22)(23)(24). Together, these observations suggest that variations in DN T cell proportion correlate with susceptibility to autoimmune diabetes.…”
mentioning
confidence: 53%
“…Because of these challenges, we instead opted to take advantage of the 3A9 TCR transgenic mouse model, in which the TCR recognizes a peptide from HEL in the context of I-A k (29), allowing to investigate the genetic regulation of the proportion of DN T cells in secondary lymphoid organs. Indeed, as for other TCR transgenic systems (15,(38)(39)(40)(41)(42)(43), the 3A9 TCR transgenes enhance the proportion of DN T cells in peripheral lymphoid organs and preclude the differentiation of potentially contaminating NKT cells, increasing the sensitivity of detection of DN T cells (22)(23)(24). We thus performed an F2 out- cross of the 3A9 TCR B10.BR and 3A9 TCR NOD.H2 k parental strains, because they exhibit a significant difference in the proportion of 3A9 DN T cells in the lymph nodes (22 k ) mice varies from 5 to 34% and presents with a Gaussian distribution (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 NOD.H 2k but not in B10.Br control mice. They also showed that IL-10 produced by these cells favours their apoptosis and hence helps to regulate their number [75]. In another study by Duncan …”
Section: Dn T Cells As the Saviours Of The Immune Systemmentioning
confidence: 99%
“…DN Tregs can suppress Ag-specific auto-, allo-or xeno-reactive CD8 1 [3,5,6], CD4 1 T cells [6][7][8][9] or B cells [10,11] in several animal models and humans. The number of DN Tregs is significantly reduced in both NOD mice as well as in TCR Tg autoimmunediabetes-prone mouse models compared with autoimmunediabetes-resistant strains [5,10]. A single transfer of DN Tregs could prevent the onset of type I diabetes in mice [5].…”
Section: Introductionmentioning
confidence: 99%